RELIGIOSITY AND CELEBRITY WORSHIP RELATIONSHIP: A STUDY OF 2PM BOYBAND FANS COMMUNITIES - Wahyu Sitasari, Novendawati; Margarett; Safitri; Lisdayanti, Annisa (International Journal of Psychosocial Rehabilitation, 2020)
In the 2PM fan community known as All Indonesia Hottest United (AIHU) which has been established since 2012 there are approximately 52 active members. With the age of 2PM boy band who had stepped on 10 years in 2018 still found fans who are quite active. The purpose of this study is to look at the relationship between religiosity and celebrity worship among members of the AIHU community. This research is quantitative, using a non-experimental correlational method with sampling techniques saturated sampling techniques because the total population is only 52 subjects and the entire population is sampled. The scale of religiosity is based on Glock & Stark theory with a number of 22 valid items with a reliability coefficient (α) of 0.874. The celebrity worship scale uses the Celebrity Attitude Scale from Maltby et al (2006) with a total of 23 valid items with a reliability coefficient (α) of 0.899. The results showed p = 0,000 with a correlation coefficient of -0.626, meaning that the hypothesis was accepted that there was a significant negative relationship between religiosity and celebrity worship on AIHU members. Based on the value of R2 shows that religiosity contributed 39% in influencing celebrity worship, while 61% was influenced by other factors. Religiosity among members of the AIHU community tends to be high and celebrity worship to members of the AIHU community tends to be low. Statistical test results state, the most dominant dimension of celebrity worship in 2PM community members is the intense-personal dimension with a percentage of 42.3%